2008
DOI: 10.1007/s00228-008-0552-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose regimens of esomeprazole for gastric acid suppression with minimal influence of the CYP2C19 polymorphism

Abstract: It was confirmed that intragastric pH values and plasma esomeprazole concentrations potentially depended on the CYP2C19 genotype status for treatment with esomeprazole. Dosage regimens of divided doses of 20TD or 10Q4D esomeprazole yielded improved antisecretory effects with a minimal influence of CYP2C19 polymorphisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 23 publications
1
37
1
2
Order By: Relevance
“…Similarly, the AUC following the administration of equal doses of pantoprazole in PM was sixfold higher than NM and IM [43,44]. Although reports have documented the impact of CYP2C19 genotype on PK for both rabeprazole [40,4549] and esomeprazole [50,51], these associations with PK parameters such as AUC were of smaller magnitude than the effects reported for other PPIs, suggesting less influence of CYP2C19 genotype on these newer generations PPIs. This is not surprising given that rabepeprazole and esomeprazole are less dependent on CYP2C19 for their metabolism (Table 1).…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, the AUC following the administration of equal doses of pantoprazole in PM was sixfold higher than NM and IM [43,44]. Although reports have documented the impact of CYP2C19 genotype on PK for both rabeprazole [40,4549] and esomeprazole [50,51], these associations with PK parameters such as AUC were of smaller magnitude than the effects reported for other PPIs, suggesting less influence of CYP2C19 genotype on these newer generations PPIs. This is not surprising given that rabepeprazole and esomeprazole are less dependent on CYP2C19 for their metabolism (Table 1).…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Some reports have shown that variations in acid suppression are less significant when PPIs with less CYP2C19 dependent metabolism such as rabeprazole [27,4749] or esomeprazole [50,52,53], are administered. CYP2C19 genotype dependent variation in median gastric PH was less for esomeprazole and rabeprazole compared to omeprazole and lansoprazole [51].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
See 3 more Smart Citations